2013
DOI: 10.1158/1535-7163.mct-13-0424
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Wee1 Sensitizes Cancer Cells to Antimetabolite Chemotherapeutics In Vitro and In Vivo, Independent of p53 Functionality

Abstract: Inhibition of Wee1 is emerging as a novel therapeutic strategy for cancer, and some data suggest that cells with dysfunctional p53 are more sensitive to Wee1 inhibition combined with conventional chemotherapy than those with functional p53. We and others found that Wee1 inhibition sensitizes leukemia cells to cytarabine. Thus, we sought to determine whether chemosensitization by Wee1 inhibition is dependent on p53 dysfunction and whether combining Wee1 inhibition is tolerable and effective in vivo. Synergistic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
99
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 26 publications
(44 reference statements)
10
99
1
Order By: Relevance
“…36,40,51,52 The combined cytarabine and MK-1775 treatments resulted in synergistic inhibition of proliferation, regardless of p53 status. 40 It has been demonstrated that cytarabine-induced S-phase cell cycle arrest was overcome by the addition of MK-1775.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…36,40,51,52 The combined cytarabine and MK-1775 treatments resulted in synergistic inhibition of proliferation, regardless of p53 status. 40 It has been demonstrated that cytarabine-induced S-phase cell cycle arrest was overcome by the addition of MK-1775.…”
Section: Discussionmentioning
confidence: 98%
“…36,40,51,52 The combined cytarabine and MK-1775 treatments resulted in synergistic inhibition of proliferation, regardless of p53 status. 40 It has been demonstrated that cytarabine-induced S-phase cell cycle arrest was overcome by the addition of MK-1775. 40, 51,52 Tibes et al used an RNAi screening approach to identify kinases involved in cytarabine sensitivity and found ATR, PKMYT1, and CHK1, among others, as kinases involved in cytarabine sensitivity.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…13 Several clinical trials are underway combining MK-1775 with conventional chemotherapy agents such as gemcitabine, where the effects relieving Weel 0 s restraint of Cdk2 during S-phase might be particularly relevant. 7,15,20,22 There is also a longstanding interest combining checkpoint inhibitors with radiotherapy, since this might differentially improve the radiation response of p53-deficient cancers, where the G1 checkpoint that normally facilitates repair is compromised. Here the anticipated effect of Wee1 inhibition would be to abrogate the G2 checkpoint, resulting in cells entering mitosis with unresolved radiation-induced chromosomal damage, and thereby undergoing death through mitotic catastrophe.…”
Section: Introductionmentioning
confidence: 99%